Uji Aktivitas Antioksidan Ekstrak Buah Kluwih (Artocarpus Communis) - Arif, Mohammad; Rahman, Nurdin; Supriadi, Supriadi (Universitas Tadulako, 2018)
This study aimed to determine antioxidant activity of artocarpus camansi fruit extracts from Sigi, Central Sulawesi. This study was conducted by maceration extraction technique, and 2,2-diphenyl-1-picrylhydrazyl (DPPH) as the source of free radicals, and vitamin C as a positive control. UV-Vis spectrophotometer was used for measuring the absorbance of artocarpus camansi fruit extracts. artocarpus camansi fruit powder was extracted by maceration using ethanol. Various concentrations of artocarpus camansi fruit extracts used were 20, 40, 60, and 80 mg/L. The results showed that the IC50 value for artocarpus camansi (artocarpus communis) fruit extract was 88.715 mg/L, whereas the IC50 value for vitamin C was 37.153 mg/L. Artocarpus camansi (artocarpus communis) fruit extracts are powerful antioxidants category based on IC50 value. The optimum percentage antioxidant activity of artocarpus camansi fruit extracts to inhibit free radical amounted to by 50.65%